Projeto habitacional dona Amélia: sistema construtivo em woodframe - Lemes, Nivaldo Roel [UNESP]; Lopes, Anderson Giovani [UNESP]; Martins, Joelmir [UNESP]; Araujo, Victor Almeida de; Vasconcelos, Juliano Souza; Vivan, André Luiz; Gava, Maristela [UNESP]; Barbosa, Juliana Cortez [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Project created with social approach to build housing in Woodframe for needy families, residents initially Itapeva-SP, with the help of materials donation as wood for the structure, floors, wires for electrical, etc. from companies and shops in town.

Projeto criado com enfoque social de construir habitações em Woodframe para famílias carentes, residentes inicialmente em Itapeva-SP, com auxílio de doação de materiais como madeira para a estrutura, pisos, fios para parte elétrica, etc. provenientes de empresas e lojas da cidade.
Keywords: Project; Woodframe; Itapeva; Projeto; Woodframe; Itapeva